System Integrity Protection by Orbital Grid-forming Mode for VSC - Lorz, Tobias; Jaworski, Michael; Jäger, Johann (16th International Conference on Developments in Power System Protection (DPSP 2022), 2022)
The primary challenge is to develop a protective function that utilises a VSC for fulfilling this task of dynamic system stabilization. In consequence, the protection function is realized in form of a converter control scheme that enables the VSC's operation in grid-forming mode (OGM) alongside with the synchronous generator. The Orbital Grid-forming mode OGM offers current limitation without a separate control-loop and even without measuring the current. Furthermore, it enables the VSC to stabilize electromechanical dynamics of synchronous machines by obtaining a maximum angular deviation between its internal voltage and their rotors. This means a generator cannot lose synchronism to the VSC and its rotor experiences a floating anchorpoint, which hinders its acceleration or deceleration until the dynamic excursion of the machine is over.
CRIS-Team Scopus Importer:2024-12-16
Keywords: GRID-FORMING; POWER SYSTEM RESTORATION; ROTOR ANGLE STABILITY; SYSTEM INTEGRITY PROTECTION